Germination, Attachment and Development of Striga hermonthica (Del.) Benth Induced by Host and Non-host Crops - Abbasher, Abbasher A.; Zaroug, Mohamed S. A.; Zahran, Eldur B.; Sauerborn, Joachum (University of Khartoum Journal of Agricultural Sciences, 2023)
Striga hermonthica (Del) Benth is a semi-parasitic weed that reduces yields of sorghum, maize, pearl millet, sugarcane and rice in the semi-arid tropics. Germination of striga seed is induced by stimulants exuded by roots of host and non-host plants. The objectives of this study were to compare the ability of some host and non-host crops to induce striga seed germination and haustoria formation as well as to confirm the susceptibility of wheat and barley to infestation. S. hermonthica seeds were collected from Abu Haraz, Gezira State, Sudan, in 2004/2005, and their germination on some host and non-host crops was investigated using root chambers that allow observation of striga underground stages. Striga seeds germinated with all tested crops. Besides sorghum varieties and maize, S. hermonthica germinated, attached and developed to complete striga plants with barley and two cultivars of wheat from Sudan. This is the first report of S. hermonthica parasitizing wheat and barley in Sudan. Use of root chambers proved that some leguminous crops were susceptible to S. hermonthica. Chick pea (Cicer arietinum L.), phillipesera (Vigna trilobata L.), brown seed cowpea [Vigna unguiculata (L.) Walp.], hyacinth bean (Lablab purpureus L.), peas (Pisum sativum L.) pigeon pea (Cajanus cajan L.), faba bean and mung bean induced seed germination, attachment and development of complete green striga plants. Soybean, roselle, safflower and sunflower supported germination and attachment of S. hermonthica, but there was no further development of the semi-parasitic weed. A natural brownish colouration around the